PENGARUH PEMBERIAN PUPUK KANDANG TERHADAP PERTUMBUHAN DAN PRODUKSI TIGA VARIETAS SAWI (Brassica juncea L.) - Ayustin Ronauli Boang Manalu (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2020)
Mustard Greens (Brassica juncea L.) is one of the vegetables that favored by the people. Commonly cultivated inorganicly. Utilizing inorganic substances continually will damage the soil. Cultivation inorganicly also will produce unhealty vegetable to consume continually. The purpose of this examination is to study the response of manure apllication on growth and production of three variety of mustard greens (Brassica juncea L.) The examination starts September until November in 2019. The examination also use Complete Random Factorial Plan with two factor. The first factor is mustard varieties which is consist of Tosakan, Sawindo and Shinta. The second factor is 0 g of manure, 30 g chiken manure, cow manure and goat manure. The result is deliver Tosakan, Sawindo and Shinta has obvius differ in amount and width of the leaves. Application of chicken manure increase mustard’s height, amount and width of leaves, moist weight, biomass weight and fresh per sampel, harvest index, root’s volume and dry weight. Variety’s interaction of chicken manure produce widest leaves and highest fresh sell’s weight.